2019
DOI: 10.1103/physrevlett.123.217001
|View full text |Cite
|
Sign up to set email alerts
|

Insulator-Metal Transition and Topological Superconductivity in UTe2 from a First-Principles Calculation

Abstract: We theoretically study superconductivity in UTe2, which is a recently discovered strong candidate for an oddparity spin-triplet superconductor. Theoretical studies for this compound faced difficulty because first-principles calculations predict an insulating electronic state, incompatible with superconducting instability. To overcome this problem, we take into account electron correlation effects by a GGA+U method and show the insulatormetal transition by Coulomb interaction. Using Fermi surfaces obtained as a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
111
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(133 citation statements)
references
References 52 publications
18
111
4
Order By: Relevance
“…Therefore, an insulating band structure of UTe 2 results in strong mixing between the conduction bands and 5 f electrons. The calculated insulating ground state for UTe 2 are also confirmed by other calculations in the framework of a density functional theory (DFT), then DFT+U calculations have been performed [13,14]. Both calculations show metallic band structures with increasing effective U, then the cylindrical Fermi surfaces like Fig.…”
Section: Band Structure and Fermi Surfaces Of Thtesupporting
confidence: 74%
See 2 more Smart Citations
“…Therefore, an insulating band structure of UTe 2 results in strong mixing between the conduction bands and 5 f electrons. The calculated insulating ground state for UTe 2 are also confirmed by other calculations in the framework of a density functional theory (DFT), then DFT+U calculations have been performed [13,14]. Both calculations show metallic band structures with increasing effective U, then the cylindrical Fermi surfaces like Fig.…”
Section: Band Structure and Fermi Surfaces Of Thtesupporting
confidence: 74%
“…4 are obtained with U = 2.0 eV by Ishizuka et al (Fig. 2 (d) [13]) and with U = 7 eV by Xu et al (Fig. 4 (a) [14]).…”
Section: Band Structure and Fermi Surfaces Of Thtementioning
confidence: 82%
See 1 more Smart Citation
“…The recent discovery of unconventional superconductivity (SC) in the uranium chalcogenide paramagnet UTe 2 with a superconducting transition temperature of T SC ∼ 1.6 K [1][2][3] opens new perspectives on superconducting topological properties including emergent Majorana quasiparticles at the verge of magnetic and electronic instability. Transport and thermodynamic measurements demonstrated that correlations play an important role in this system, requiring theoretical treatment beyond the local-density approximation approach [2,[4][5][6][7][8]. The closeness of UTe 2 to ferromagnetic quantum criticality [9] induces astonishing superconducting properties.…”
Section: Introductionmentioning
confidence: 99%
“…Recently a new member of a superconductor UTe 2 with T c =1.6K 2,3 is discovered, which is almost ferromagnetic, and attracts much excitement. Many researchers start devoting to UTe 2 experimentally 4-16 and theoretically [17][18][19] and show renewed interest on the former three compounds too. Those heavy Fermion materials belong to a strongly correlated system where 5f electrons responsible for it is believed to form a coherent narrow band with the large mass enhancement below a Kondo temperature.…”
mentioning
confidence: 99%